Cross-sectional associations between maternal self-efficacy and dietary intake and physical activity in four-year-old children of first-time Swedish mothers. (1st June 2018) - Rohde, Jeanett Friis; Bohman, Benjamin; Berglind, Daniel; Hansson, Lena M.; Frederiksen, Peder; Mortensen, Erik Lykke; Heitmann, Berit Lilienthal; Rasmussen, Finn
Abstract: Background: Healthy dietary and physical activity behaviours are established early in life where children learn by observing their parents. Therefore, parents can act as role models and influence their children toward a healthier lifestyle. Besides a strong association between parental and child health behaviours, parents also influence their children's health behaviours through socio-cognitive processes, where perceived self-efficacy is the central component. The objective was to examine if parental self-efficacy among Swedish mothers was associated with their four-year-old children's dietary and physical activity behaviours. Methods: This cross-sectional study was based on information from control participants that took part in the Swedish primary prevention trial of childhood obesity (PRIMROSE) (n = 420 mother-child pairs). Linear regression models were used to examine the associations between parental self-efficacy (Parental Self-Efficacy for Promoting Healthy Physical Activity and Dietary Behaviours in Children Scale) and children's dietary intake (parent reported) and levels of physical activity (accelerometer) with adjustments for potential confounders. Results: Mothers' efficacy beliefs in promoting healthy dietary or physical activity behaviours in their children were associated with a slightly higher consumption of fruit and vegetables among their children (β: 0.03 [95%CI: 0.01; 0.04] P < 0.001) and slightly higher levels of moderate-to-vigorous activity (β: 0.43 [95%CI: 0.05; 0.81] P = 0.03). Mothers' belief in their ability to limit unhealthy dietary and physical activity behaviours was inversely associated with children's intake of unhealthy snacks (β: −0.06 [95%CI: −0.10; −0.02] P < 0.01). Conclusion: Our cross-sectional study suggests weak positive correlations between maternal self-efficacy and healthy dietary and physical activity behaviours, and weak inverse associations between maternal self-efficacy and unhealthy dietary and physical activity behaviours among their children.